HIV/AIDS and family support systems: A situation analysis of people living with HIV/AIDS in Lagos State - Adeyemi E. Oluwagbemiga (Taylor & Francis Group, 2007)
Current statistics about the HIV/AIDS epidemic in Nigeria do not reveal the broader social and economic impacts of the disease on the family. The study therefore primarily aimed to address the socio-economic effects of HIV infection on individuals and their families. The study was carried out in Lagos State. In-depth interviews were employed to collect information from 188 people living with HIV/AIDS through support groups in the state, while four focus group discussions were conducted to elicit information from people affected by AIDS about the socio-economic impacts of HIV/AIDS on families in Nigeria. From the survey, among people living with HIV/AIDS, 66% of females and males were in the age group 21-40 years, while 10% were older people above 60 years of age. Findings revealed that as HIV/AIDS strikes at parents, grand parents are assuming responsibility for bringing up the children of the infected persons and the orphans of those killed by the virus. It was striking that some of the older caregivers could not meet the requirement of these children. They are often forced to work more than they would have, or borrow in order to cope with the needs of these extra mouths. Some of the infected people have sold their properties to enable them to cope with the economic effects of the virus, while their children have had to drop out of school, since they could not afford the school fees and other related expenses. It was suggested that PLWHA should be economically empowered with adequate medical treatment, in order to reduce the impact of the disease on the family.